Hydrogen activated the Nrf2/HO pathway to alleviate the cognitive decline in PD Drosophila after long-term sevoflurane exposure. - Li, M.; Ma, B.; Liang, S.; Pan, X.; Xie, J.; Wang, H.; Guo, J. (Neurotoxicology and teratology, 2025)
The demand for surgical and anesthetic care in patients with Parkinson's disease (PD) is projected to increase, because PD is the fastest-growing neurological disorder. Sevoflurane, the most commonly used volatile anesthetic, is neurotoxic to human and animal neonatal brains. Moreover, sevoflurane-based anesthesia can induce postoperative delirium (POD) in patients with PD. Therefore, our study was aimed at finding an effective treatment for sevoflurane-induced neurotoxicity in patients with PD by using a PD-POD Drosophila model. The small gas, hydrogen (H2), was found to ameliorate learning and memory impairment, and increase the lifespan of PD flies, after long-term sevoflurane exposure. The performance index of the PD-POD flies increased by 30 % after H2 inhalation. Moreover, H2 inhalation decreased oxidative stress levels in PD fly brains, and increased electron transport chain and OXPHOS efficiency, as well as ATP synthesis, thus indicating enhanced mitochondrial function. In addition, PD flies with H2 inhalation after sevoflurane exposure showed increased nuclear levels of Nrf2 and expression of its downstream target HO. Therefore, H2 might exert antioxidant effects by activating the Nrf2/HO pathway, thereby decreasing oxidative stress levels and apoptosis in PD fly brains after long-term sevoflurane treatment. Inhalation of H2 is likely to be an effective and convenient method to alleviate the neurotoxicity effects or POD caused by long-term sevoflurane exposure.